2023
DOI: 10.1007/s40265-023-01926-0
|View full text |Cite|
|
Sign up to set email alerts
|

Remdesivir: A Review in COVID-19

Hannah A. Blair

Abstract: Remdesivir (Veklury ® ), a nucleotide analogue prodrug with broad-spectrum antiviral activity, is approved for the treatment of coronavirus disease 2019 (COVID-19), the illness caused by severe acute respiratory syndrome coronavirus 2 infection. Unlike some antivirals, remdesivir has a low potential for drug-drug interactions. In the pivotal ACTT-1 trial in hospitalized patients with COVID-19, daily intravenous infusions of remdesivir significantly reduced time to recovery relative to pl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(10 citation statements)
references
References 123 publications
0
8
0
2
Order By: Relevance
“…However, the data presented herein demonstrated that the potency and toxicities of some drugs, especially NA inhibitors were cell-system dependent. This was not unexpected since different cell types may have unequal distributions of drug metabolizing enzymes and membrane transporters [ 201 ], and certain antiviral agents (e.g., remdesivir and nirmatrelvir) are substrates of the Cytochrome P450 enzymes, P-glycoprotein, and other cell membrane transporters [ 202 , 203 ]. Also, NA phosphorylation may be cell-dependent [ 138 , 139 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, the data presented herein demonstrated that the potency and toxicities of some drugs, especially NA inhibitors were cell-system dependent. This was not unexpected since different cell types may have unequal distributions of drug metabolizing enzymes and membrane transporters [ 201 ], and certain antiviral agents (e.g., remdesivir and nirmatrelvir) are substrates of the Cytochrome P450 enzymes, P-glycoprotein, and other cell membrane transporters [ 202 , 203 ]. Also, NA phosphorylation may be cell-dependent [ 138 , 139 ].…”
Section: Discussionmentioning
confidence: 99%
“…Coronavirus disease 2019 (COVID-19) is an infectious disease caused by severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) infection 81 . With a significant increase in the number of cases around the world since its first appearance in 2019, the rapid spread of COVID-19 has had a major influence on human health, the economy, education, and social development worldwide 82 .…”
Section: Application Of Electrochemical Protein Sensors In the Detect...mentioning
confidence: 99%
“…It improves recovery time in hospitalized patients, potentially provides a mortality benefit for patients with minimal oxygen requirements, and reduces the risk of hospitalization or death in outpatients at high risk for disease progression. 9 …”
Section: Introductionmentioning
confidence: 99%